Community-acquired pneumonia severity assessment tools in patients hospitalized with COVID-19: a validation and clinical applicability study. (July 2021) - Lazar Neto, Felippe; Marino, Lucas Oliveira; Torres, Antoni; Cilloniz, Catia; Meirelles Marchini, Julio Flavio; Garcia de Alencar, Julio Cesar; Palomeque, Andrea; Albacar, Núria; Brandão Neto, Rodrigo Antônio; Souza, Heraldo Possolo; Ranzani, Otavio T.; ,; et al.
Abstract: Objective: To externally validate community-acquired pneumonia (CAP) tools on patients hospitalized with coronavirus disease 2019 (COVID-19) pneumonia from two distinct countries, and compare their performance with recently developed COVID-19 mortality risk stratification tools. Methods: We evaluated 11 risk stratification scores in a binational retrospective cohort of patients hospitalized with COVID-19 pneumonia in São Paulo and Barcelona: Pneumonia Severity Index (PSI), CURB, CURB-65, qSOFA, Infectious Disease Society of America and American Thoracic Society Minor Criteria, REA-ICU, SCAP, SMART-COP, CALL, COVID GRAM and 4C. The primary and secondary outcomes were 30-day in-hospital mortality and 7-day intensive care unit (ICU) admission, respectively. We compared their predictive performance using the area under the receiver operating characteristics curve (AUC), sensitivity, specificity, likelihood ratios, calibration plots and decision curve analysis. Results: Of 1363 patients, the mean (SD) age was 61 (16) years. The 30-day in-hospital mortality rate was 24.6% (228/925) in São Paulo and 21.0% (92/438) in Barcelona. For in-hospital mortality, we found higher AUCs for PSI (0.79, 95% CI 0.77–0.82), 4C (0.78, 95% CI 0.75–0.81), COVID GRAM (0.77, 95% CI 0.75–0.80) and CURB-65 (0.74, 95% CI 0.72–0.77). Results were similar for both countries. For the 1%–20% threshold range in decision curve analysis, PSI would avoid a higher number of unnecessary interventions, followed by the 4C score. All scores had poor performance (AUC <0.65) for 7-day ICU admission. Conclusions: Recent clinical COVID-19 assessment scores had comparable performance to standard pneumonia prognostic tools. Because it is expected that new scores outperform older ones during development, external validation studies are needed before recommending their use.